Matching Service Offerings and Product Operations: A Key to Servitization Success: Existing conditions, such as product characteristics or market attributes, may determine the success of a move toward servitization. Issue 3 (3rd May 2016) - Jovanovic, Marin; Engwall, Mats; Jerbrant, Anna
OVERVIEW: Many manufacturers are moving to servitization, but making that move successfully requires considering the underlying business logic of a division or product. Differences in existing conditions, such as product characteristics or other business attributes, may determine success in transition to a services-based business model and create challenges for a firm moving, for instance, from a spare-parts model to advanced service contracts. Our study pinpoints a number of key product attributes that define how far a company can move up the service ladder. The findings suggest that the Power-by-the-Hour model pioneered by Rolls-Royce suits products that constitute critical ancillary input to, and not essential elements of, customers' core processes; that require low initial investments relative to high total costs of ownership; that are used in controllable operating environments with measurable performance requirements; and that are associated with high risk and high costs in the event of failure. Further, the service delivery system must be integrated and orchestrated to be product-specific—that is, aligned with the function and operating conditions of the product in use.